Can Social Protection Improve Sustainable Development Goals for Adolescent Health? - Cluver, L.; Orkin, F.; Meinck, F.; Boyes, Mark; Yakubovich, A.; Sherr, L. (Public Library of Science, 2016)
BACKGROUND: The first policy action outlined in the Sustainable Development Goals (SDGs) is the implementation of national social protection systems. This study assesses whether social protection provision can impact 17 indicators of five key health-related SDG goals amongst adolescents in South Africa. METHODS: We conducted a longitudinal survey of adolescents (10-18 years) between 2009 and 2012. Census areas were randomly selected in two urban and two rural health districts in two South African provinces, including all homes with a resident adolescent. Household receipt of social protection in the form of 'cash' (economic provision) and 'care' (psychosocial support) social protection, and health-related indicators within five SDG goals were assessed. Gender-disaggregated analyses included multivariate logistic regression, testing for interactions between social protection and socio-demographic covariates, and marginal effects models. FINDINGS: Social protection was associated with significant adolescent risk reductions in 12 of 17 gender-disaggregated SDG indicators, spanning SDG 2 (hunger); SDG 3 (AIDS, tuberculosis, mental health and substance abuse); SDG 4 (educational access); SDG 5 (sexual exploitation, sexual and reproductive health); and SDG 16 (violence perpetration). For six of 17 indicators, combined cash plus care showed enhanced risk reduction effects. Two interactions showed that effects of care varied by poverty level for boys' hunger and girls' school dropout. For tuberculosis, and for boys' sexual exploitation and girls' mental health and violence perpetration, no effects were found and more targeted or creative means will be needed to reach adolescents on these challenging burdens. INTERPRETATION: National social protection systems are not a panacea, but findings suggest that they have multiple and synergistic positive associations with adolescent health outcomes. Such systems may help us rise to the challenges of health and sustainable development.